EDUKASI PEMBUATAN HAND SANITIZER DARI TANAMAN SEREH WANGI (Cymbopogon nardus) PADA SANTRIWATI PONDOK PESANTREN ASY SYAFI’I - Anung Kustriyani; Dita Amanda Deviani; Nina Wijiani; Abi Mas Udianto; Anggie Andina Ritansa; I Gede Agus Alam Arimbawa; Muhammad Dzikry Alfiyansyah (LPPM Universitas dr. Soebandi, 2023)
The number of positive cases of COVID-19 is still being reported in Indonesia. However this number has decreased significantly compared to the previous time. Prevention efforts are still being carried out by the government in suppressing the number of COVID-19. One of the efforts is the Clean and Healthy Lifestyle (PHBS). An example of PHBS is to use hand sanitizer. People can use hand sanitizer if there is no place to wash their hands with soap and water. The manufacture of hand sanitizers has also developed by utilizing herbal plants. This herbal plant certainly has medicinal and antibacterial properties. This plant can also be cultivated around the yard of the house. The purpose of this activity is to optimize the use of Sereh Wangi into pharmaceutical dosage forms that are useful for the community. The methods are counseling activities, guidance and manufacturing practices, and the provision of hand sanitizers. The students of the Asy Syafi'i Islamic Boarding School have knowledge about other benefits of Sereh Wangi after participating in community service. Santriwati feels happy because she can make and apply the products that have been made by herself.